SANKSI PRODUK YANG TIDAK BERLEBEL HALAL - Mospa Darma (Universitas Islam Sumatera Utara, 2020)
In the world of business producers are vying to meet the needs of producers who are certain to be a benchmark in economic principles where suply depends on dimand, on the other hand demand depends on the needs of the community but all market demand is determined by the regulation applied by producers and governments.